COHERENCE LEVEL PADA DRAFT PROPOSAL SKRIPSI MAHASISWA PENDIDIKAN BAHASA INGGRIS UNIMUS - Muhimatul Ifadah; Dian Candra P (Universitas Muhammadiyah Semarang, 2014)
Communicative competence may be represented by the meaning or message delivered by the interlocutor in the spoken language or the writer in the written language. Though, in the written language, the lexical choice and the coherence which is employed by cohesive devices determine the readers’ expectation in understanding a text. In the final project proposal of English education program, the cohesive devices were identified, classified, calculated and interpreted to drawing conclusion. It was found that the highest percentage of ties was causal, followed by additive, adversative and temporal was the least. In the level of wording,conjunction used most to develop coherence rather than ellipsis. However, the final project was actually represented the level of understanding and competence of the students in writing, and it also may represented the portrait of learning evaluation from writing skill. It needs more timeand practices to write an acceptable written text which is culturally and semantically appropriate as English is not as a second language, but foreign language.